IMPLEMENTATION OF THE COOPERATIVE LEARNING METHOD IN TEACHING READING COMPREHENSION - Rifky Haydan (Journal of English and Education, 2013)
The present study reported the use of cooperative learning method in improving students’ reading comprehension. The research was conducted to find out whether or not cooperative learning improved students’ reading comprehension, and to find out students’ responses toward the implementation of cooperative learning methods. The design employed in this research was Classroom Action Research. The study was conducted at XI Grade of Culinary Class which involved thirty one students. Observation checklists, students’ questionnaire, evaluation sheet and students’ reading test were implemented as instruments to collect the data. The findings of the study showed that cooperative learning methods (STAD and Jigsaw) improved the students’ comprehension in reading descriptive text. On the first cycle, there were 13 students (42%) who passed the reading posttest, while in cycle 2, the students who passed the reading posttest were 25 students (86%).The findings also showed that the students gave positive responses since they stated that cooperative learning methods were fun and helped them in understanding descriptive texts and they wanted to know more about it. Keywords: Cooperative Learning, reading, descriptive text